Pengaruh brand awareness terhadap minat pembelian pada usaha kreatif Pathi’s Chocolade di Sidoarjo Jawa Timur - Irawan, Pristanto Ria; Abdillah, Abdillah; Taryanto, Taryanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine the extent of brand awareness in Pathi's chocolade creative business, purchase interest in Pathi's chocolade creative business, and the influence of brand awareness on purchase interest in Pathi's chocolade creative business in Sidoarjo, East Java. This study uses a quantitative descriptive method with data collection techniques through the distribution of questionnaires, and library data. In this study, the sample used was 100 customers. The data analysis technique used was simple linear regression analysis using the SPSS application. The results show that (1) the brand awareness variable has a good category assessment score with an average score of 49.1 questionnaire results (minimum score range of 28-maximum 60), (2) the purchase interest variable has a good rating category with an average score of the questionnaire results. 49.3 (minimum score range of 28-maximum 60), and (3) there is an influence of brand awareness of 64.3% on purchase intention, while the remaining 35.7% which is influenced by other factors is not examined in this study.